Identification of the Customers’ Preferred Attributes while Selecting an OTA (Online Travel Agency) Platform - Sharma, Animesh Kumar; Sharma, Rahul (Indian Journal of Marketing, 2022)
This paper aimed to identify customers’ preferred attributes when selecting an online travel agency’s platform. The use of online travel agency platforms is increasing rapidly among travelers to search for information related to holiday packages, availability of flights, hotel bookings, itinerary details, etc. The online travel business is forecasted to touch 820.18 billion by 2023, highlighting the need to study the OTA attributes. Multiple online travel agency platforms have entered the market, making it extremely important to identify attributes of OTA platforms that play a part in shaping consumer purchase intention. This study will help online travel service providers understand the attributes preferred by customers when opting for an online travel agency. The research findings highlighted different attributes and their subsequent levels in influencing customers’ choices.